2015
DOI: 10.1007/s13404-015-0165-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of a synthetic foot-and-mouth disease virus peptide conjugated to gold nanoparticles for enhancing immunological response

Abstract: Foot-and-mouth disease is an acute, highly contagious infection of domestic and wild cloven-hoofed animals, which can be transmitted to humans. In many cases, the existing vaccines are not quite effective. The purpose of this study was to test the possibility of using gold nanoparticles as an antigen carrier and an adjuvant. The immunogenic properties of gold nanoparticles were assessed by conjugating the particles to a synthetic peptide of the VP 1 capsid protein of the foot-and-mouth disease virus. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Control experiments showed that the observed specificity of antisera against Ara 6 -GNPs 3 and 4 is due to the presence of the Ara 6 -epitope in Ara 6 -GNPs 3 and 4 and is not related to the presence of background anti-mycobacterial antibodies, which could be present in intact rabbit serum used for immunization, or antibodies generated against heat-inactivated M. tuberculosis cells, which are present in CFA ( Figure 6, Supporting Information File 1, Figure S1). The importance of using CFA for the generation of hapten-specific antibodies has been recently demonstrated [77]. The titers of antibodies against haptens amine-linked to GNPs decreased in the following order: (hapten + GNPs + CFA) > (hapten + GNPs) ≫ (hapten + CFA).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Control experiments showed that the observed specificity of antisera against Ara 6 -GNPs 3 and 4 is due to the presence of the Ara 6 -epitope in Ara 6 -GNPs 3 and 4 and is not related to the presence of background anti-mycobacterial antibodies, which could be present in intact rabbit serum used for immunization, or antibodies generated against heat-inactivated M. tuberculosis cells, which are present in CFA ( Figure 6, Supporting Information File 1, Figure S1). The importance of using CFA for the generation of hapten-specific antibodies has been recently demonstrated [77]. The titers of antibodies against haptens amine-linked to GNPs decreased in the following order: (hapten + GNPs + CFA) > (hapten + GNPs) ≫ (hapten + CFA).…”
Section: Discussionmentioning
confidence: 99%
“…In order to prepare the glyco-GNPs, Ara 6 glycosides 1 and 2 ( Figure 1) were directly conjugated to pre-formed [67,94] freshly prepared citrate-stabilized spherical gold nanoparticles (d = 15 nm, identical to those prepared earlier [77]) to give the corresponding Ara 6 -GNPs 3 and 4 (Figure 1), which have the same size as the parent GNPs according to transmission electron microscopy (TEM) ( Figure 2).…”
Section: Glyco-gnpsmentioning
confidence: 99%
See 3 more Smart Citations